Role of Combined Circumareolar Skin Excision and Liposuction in Management of High grade Gynaecomastia - Sarkar, Arindam (Medknow Publications & Media Pvt Ltd, 2014)
INTRODUCTION: High-grade gynaecomastia (Simon IIb and III) has tissue excess (skin excess, enlarged areola, and displaced nipple), which is best managed surgically; however, results of conventional breast reduction surgeries and liposuction is not very good. Aim of our study was to describe a combined technique to manage these problems to produce a good result. MATERIAL AND METHOD: This was a 2-year study among 12 patients of high grade gynaecomastia. Clinical and laboratory findings were normal. Pre-operatively in standing position, diameter of breast and areola, position of nipple, and amount of skin excess were marked. Under general anaesthesia, tumescent infiltration, circumareolar de-epithelisation of skin excess, and liposuction was completed. Redundant portion of the breast was sharply dissected and pulled out. Areola was fixed over pectoralis fascia at mid humerus level, just medial to the mid-clavicular line. Outer borders of the de-epithelised area were apposed by the purse-string effect of a subdermal suture, and further apposed by few half buried horizontal mattress sutures. Drains for 24 hour and compressive dressings for 6 weeks were used. RESULT: Mean age of presentation was 25.8 year; emotional discomfort was the chief complaint. Among 12 patients, 10 patients had bilateral gynaecomastia and 8 patients had enlarged and displaced nipple-areola complex. Average hospital stay was 2.41 days and recoveries were usually uneventful. CONCLUSION: The problem of tissue excess and tissue displacement in high grade gynaecomastia can be well managed by this combined circumareolar skin reduction and liposuction technique to achieve a scar-less flat male chest.